Bioaccumulation and biotransformation of decabromodiphenyl ether and effects on daily growth in juvenile lake whitefish (Coregonus clupeaformis) - Kuo, Yin-Ming (Ecotoxicology (London, England), 2010)
Decabromodiphenyl ether (BDE 209) is the main congener in the commonly used commercial flame retardant mixture, "deca-BDE". There is evidence showing that fish can debrominate BDE 209 into potentially more toxic congeners. The objective of this study was to evaluate BDE 209 uptake and its potential effects on juvenile lake whitefish (Coregonus clupeaformis). Lake whitefish were fed BDE 209 at four nominal concentrations (control, 0.1, 1, and 2 microg/g-diet) for 30 days. Livers and carcasses were analyzed for 11 polybrominated diphenyl ether (PBDE) congeners (BDE 47, 99, 100, 153, 154, 196, 197, 206, 207, 208, and 209) and daily otolith increment width was measured as an estimate of growth before and after exposure. Four congeners (BDE 206, 207, 208, and 209) were detected in livers and carcasses. Hepatic BDE 209 concentrations in the 1 and 2 microg/g treatments were significantly higher than in the control group (1.25 and 5.80 nmol/g-lipid compared to 0.183 nmol/g-lipid). The concentration of BDE 209 detected in the tissues of the control group resulted from BDE 209 in the base diets. Concentrations of all congeners from the 1 and 2 microg/g groups were higher in livers than carcasses, indicating the liver was the primary organ of BDE 209 accumulation. Compared to the fraction in diets, the molar fraction of BDE 209 was lower in livers and carcasses, whereas the fractions of BDE 206, 207, and 208 were higher. These different distributions of PBDE congeners resulted from differential adsorption and metabolism. One congener, BDE 206, could be a major metabolite from BDE 209 debromination. Otolith increment widths were narrower in fish from the highest diet concentration administered, suggesting BDE 209 may have affected growth rates. In conclusion, this in vivo study with lake whitefish showed that BDE 209 was debrominated into lower PBDE congeners and that exposure to 2 microg/g may have affected fish growth